If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 7 = 3 Reorder the terms: 7 + 5p = 3 Solving 7 + 5p = 3 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5p = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 5p = 3 + -7 5p = 3 + -7 Combine like terms: 3 + -7 = -4 5p = -4 Divide each side by '5'. p = -0.8 Simplifying p = -0.8
| 63=x | | 100-(5+5)= | | 9+7t+1+4t= | | 4x^2+40x-384=0 | | x+12=.5x(6) | | 2x^4-4x+1=0 | | -(9x-6)+9x= | | 3-4(x+2)=-(2x-3) | | x^2-16x-65=0 | | 4x^2+40x+384=0 | | (5x+2)(5x^2-4x-6)= | | 10-5.3*(-4+-6)= | | -2*(4)-3(-5)= | | 5(9-5x)-7=38 | | 2*(4)-3(-5)= | | 3(3-5x)-3=18 | | x+17-28+5=179 | | x+10+2x=180 | | 4y-2(5y+1)=16+3(4y-10) | | 7x-3y=37 | | -20-(-2)*(-6)= | | 2x+x+3x=120 | | (1/4)*(x+4)-7=(1-x)+(x-23)/4 | | 1/4*(x+4)-7=(1-x)+(x-23)/4 | | x+(2x+5)+(2x+5)=95 | | y+8=-4(x+7) | | y=(x)2-2 | | 3(4y-3)=7 | | h(t)=150t-5t | | 4-6(x-4)=2(x-4) | | 8x-92=5x-8 | | 2(-5a^2+8a-12)-(a^2-3a-7)= |